2008
DOI: 10.1590/s0104-11692008000300015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical case studies in mental health by means of the on-line discussion

Abstract: Silva EC, Furegato ARF, Godoy S. Clinical case studies in mental health through on-line discussion. Rev Latino- ESTUDOS DE CASOS CLÍNICOS EM SAÚDE MENTAL POR MEIO DE DISCUSSÃO ON-LINE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…In participants' self-assessments, we also found that the co-teaching curriculum in medicine and nursing helped to develop clinical dialectical thinking. Clinical reasoning skills refer to the ability of nurses to analyze, reason logically, make clinical judgments, and make decisions about the diagnosis and treatment of diseases to solve problems in clinical practice [ 23 ]. In clinical practice, nurses are required to be able to correctly apply nursing procedures in complex clinical scenarios, to propose solutions to different problems that exist at each stage of the patient's care, and to evaluate their effectiveness [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In participants' self-assessments, we also found that the co-teaching curriculum in medicine and nursing helped to develop clinical dialectical thinking. Clinical reasoning skills refer to the ability of nurses to analyze, reason logically, make clinical judgments, and make decisions about the diagnosis and treatment of diseases to solve problems in clinical practice [ 23 ]. In clinical practice, nurses are required to be able to correctly apply nursing procedures in complex clinical scenarios, to propose solutions to different problems that exist at each stage of the patient's care, and to evaluate their effectiveness [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas interdisciplinarity must be present at the university, and knowledge must advance from cognitive sphere to action (13,14) , subjects like Pathology and Microbiology, among others, could be better related to the practice of nursing, bringing the issues surrounding breastfeeding for the analysis of students during these contents, thus articulating the subjects offered in graduate education (15) . It was also revealed that the finding regarding the block of questions with fewer total correct answers, block "Microorganisms", differs from the previous study in a nursing graduate course of Salvador, where blocks with fewer total correct answers were medication, weaning and physiology (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Hay en este punto una indicación de que el conocimiento necesita avanzar de la esfera cognitiva para la acción. En este sentido, una investigación desarrollada con estudiantes de enfermería, reveló que el conocimiento se va construyendo progresivamente y generalmente empieza por la etapa cognitiva (11) .…”
Section: Discussionunclassified
“…En este sentido, los casos clínicos han sido utilizados con éxito en la enseñanza de contenidos del área de salud mental, pues estimulan la participación del estudiante, además de permitir el acceso a diferentes niveles de competencia (11) .…”
Section: Discussionunclassified